Pengaruh Pertumbuhan Ekonomi Dan Kebijakan Moneter Terhadap Utang Luar Negeri Di Indonesia Periode 2013-2022 - Indah Suci Romadhon; Yusran Daeng Matta (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This research aims to determine the influence of economic growth and monetary policy on foreign debt in Indonesia for the 2013-2022 period. The method used in this research is a causal associative method with a quantitative approach. Data analysis uses the classic assumption test, multiple linear regression analysis, correlation coefficient analysis, coefficient of determination analysis, hypothesis t test, and hypothesis f test. The research results show that the economic growth variable has no effect on foreign debt, while the monetary policy variable has an effect on foreign debt. Simultaneously, these two variables influence foreign debt